Validation of the observational version of the motivation for treatment scale - Gongora, Vanesa Carina (2012)
In this study, the psychometric properties of a clinician's observation version of Motivation for Treatment (MfT-O) were assessed and compared with the patient's version (MfT). The sample was composed of 243 inpatients that started inpatient treatment for substance dependence in The Netherlands. The EuropASI and the Motivation for Treatment (MfT) scales were administered to patients while the MfT-O was completed by clinicians during the first week of treatment. With minor adjustments, the MfT-O replicated the factorial structure of the MfT. The items were distributed into four scales: General Problem Recognition (PR1), Specific Problem Recognition (PR2), Desire for Help (DH), and Treatment Readiness. The MfT-O had an adequate reliability for all the scales (all >0.72). The MfT-O was related to the severity of problems as assessed by the EuropASI. The DH MfT-O scale was more predictive of time in treatment than the DH MfT scale.